Toll-Like Receptors and Diabetic Nephropathy: A Review of Recent Advances - Mohammad Sadra Gholami Chahkand; Yasaman Tavakoli; Ava Aghakhani; Monireh Askarzadeh; Hosein Azimi; Nogol Ghalamkarpour; Alaleh Alizadeh; Iman Archin; Sajad Kermani; Akram Ansari; Mohadeseh Poudineh; Zahra Mali; et al. (Turkish Journal of Immunology)
Diabetic nephropathy (DN) is one of the most common kidney diseases, but its exact pathophysiology remains unknown. Toll-like receptors (TLRs) are innate immune receptors that recognize pathogen- and danger-associated molecular patterns, which can result in an inflammatory response. TLR4, TLR2, TLR5, TLR7, TLR8, TLR9, and TLR11 are essential in the pathogenesis of DN, according to recent evidence collected from both in vivo and in vitro studies. Studies have shown that TLR2 and TLR4 expression is higher in patients with renal failure and nephrotic diabetes. They also play critical roles in podocyte injury and inflammation caused by high glucose. TLR2 and TLR4 may be helpful therapeutic targets to prevent or delay DN in patients with type 2 diabetes mellitus. Additionally, TLR7 may contribute to kidney damage in type 1 diabetes mellitus, whereas downregulation of TLR9 expression inhibits inflammation and apoptosis pathways associated with DN.